2012
DOI: 10.4049/jimmunol.1102683
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Reductase Facilitates Host Defense by Sustaining Phagocytic Oxidative Burst and Promoting the Development of Neutrophil Extracellular Traps

Abstract: Glutathione reductase (Gsr)3 catalyzes the reduction of glutathione disulfide to glutathione, which plays an important role in the bactericidal function of phagocytes. Since Gsr has been implicated in the oxidative burst in human neutrophils and is abundantly expressed in the lymphoid system, we hypothesized that Gsr-deficient mice would exhibit marked defects during the immune response against bacterial challenge. We report here that Gsr-null mice exhibited enhanced susceptibility to Escherichia coli challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 59 publications
4
60
0
1
Order By: Relevance
“…Slides were fixed with absolute ethanol, stained with Dip Quick and examined with a Zeiss Axio Scope A1 (Carl Zeiss, Thornwood, NY, USA). Percentage of phagocytosis with different treatments were manually counted from 5 random fields (100 cells per field) at 10× objective by three well-trained observers in a blinded technique (Yan et al, 2012).…”
Section: Neutrophils (25×10mentioning
confidence: 99%
“…Slides were fixed with absolute ethanol, stained with Dip Quick and examined with a Zeiss Axio Scope A1 (Carl Zeiss, Thornwood, NY, USA). Percentage of phagocytosis with different treatments were manually counted from 5 random fields (100 cells per field) at 10× objective by three well-trained observers in a blinded technique (Yan et al, 2012).…”
Section: Neutrophils (25×10mentioning
confidence: 99%
“…Studies with GSH reductase-deficient mice indicated they had an impaired oxidative burst and produced less ROM due to GSH depletion (Yan et al, 2012). In agreement with this, reduced neutrophil oxidative burst in humans was detected in response to chronic oxidative stress (Amer and Fibach, 2005).…”
Section: Blood Neutrophil and Monocyte Killing Capacitymentioning
confidence: 72%
“…Although the intensity of the oxidative burst in monocytes stimulated by E. coli has been suggested to be lower than in PMNL (Yan et al, 2012), monocytes also have the ability to phagocytose and carry out oxidative burst (Keogh et al, 2011). The fact that CHOL supplementation lead to greater monocyte oxidative burst without elevating plasma Ca 2+ suggest existence of alternative mechanisms.…”
Section: Blood Neutrophil and Monocyte Killing Capacitymentioning
confidence: 99%
“…While Sytox ® Green gives a bright green picture when excited with the 450-490 nm laser, Sytox ® Orange is excited by 520-550 nm source and gives a bright orange light [35,36]. Picogreen ® and Hoechst 33258 -based assay are also used to check the NETs-DNA [31,33,37,39]. Both dyes are ultra sensitive fluorescent nucleic acid stains for quantifying double-stranded DNA in solution.…”
Section: Attempts Of Extracellular Traps-dna Quantification Based On mentioning
confidence: 99%